Blueprint for a Rural District Based ICT Center in Mahabubnagar, Telangana State, India - Srinivas Akula; Haein Shin; Radhika Iyengar; Navatha Kanike; Tara Stafford Ocansey; Joaquin Aviles Lopez (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
This document outlines one of the Centers in operation as a part of the broader ICT Center Model1. The concept that began with the goal of combining multiple Sustainable Development Goals (SDGs) to improve educational and employment opportunities for women resulted in ICT Center, including the fully functioning ICT Women's Center in Telangana State, India. Powered by solar energy, where skills trainings offered in the areas of computer, English, life skills and environment, aim to prepare young women for future careers and job opportunities. The document outlines various components after the first year of execution of the ICT Center. It outlays a blue print for similar centers that could be set-up in smaller towns in India. It explains the vision and the mission of the ICT Center, followed by the key elements in the set-up process of the Center. Budgets and budget narrative explain the financial component of this program. It explains some of the processes followed in the first year, including inviting visitors and their interactions with the trainees. The report also outlays the Annual Calender and matches it to the curricular expectations at the Center. In addition, a vital strategy for the Center has been the solar panel installation, the data from which have been tracked since the beginning of the Center. The report presents the solar data and the energy consumption and reduction of electricity bills for the District Government. The report finally presents the curricular plans and the changes from the first year of implementation of the ICT Center. The changes were informed by the feedback from the students in the previous batches along with some new additions including environmental education for 2019-20 academic year.
Keywords: 330